2020
DOI: 10.34172/jrhs.2020.02
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Breast Cancer Screening among Married Women: A Cross-Sectional Study

Abstract: Background: Regular cancer screening is the best way for early detection of breast cancer, but studies showed the low participation rates of screening in Iran. We aimed to determine breast cancer screening among married women and related factors in North of Iran. Study design: A cross-sectional study. Methods: This cross-sectional study was carried out from Jan to Mar 2017 among 1472 married women in an urban population in Rasht City, North of Iran. Data were collected using a questionnaire included socio-demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Mammography performance was associated with the health insurance and the family history. Moreover, clinical breast examination was associated with the age of women, and the breast self-examination was associated with the age and profession of women (Ghanbari et al 2020). In another study, alcohol consumption was examined and it was found to be not associated with the breast cancer screening (Matsubara et al 2013).…”
Section: Literaturementioning
confidence: 97%
See 3 more Smart Citations
“…Mammography performance was associated with the health insurance and the family history. Moreover, clinical breast examination was associated with the age of women, and the breast self-examination was associated with the age and profession of women (Ghanbari et al 2020). In another study, alcohol consumption was examined and it was found to be not associated with the breast cancer screening (Matsubara et al 2013).…”
Section: Literaturementioning
confidence: 97%
“…In different studies, the rate of women getting mammograms varies between 3.4% and 85% (Bhandari et al 2021;Ghanbari et al 2020;Aşkın et al 2019). This arising wide ranged ratio brings these questions along: "What is the reason for such a high difference?"…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…
Cancer is the result of the outgrowth of a clonal population of cells from bodily tissue [1]. It has been acknowledged that early oncogenesis, also known as carcinogenesis, can be determined by cell-intrinsic features.
…”
mentioning
confidence: 99%